Physical activity: perceptions of people with severe traumatic brain injury living in the community. (28th January 2018) - Analytis, Penelope; McKay, Adam; Hamilton, Megan; Williams, Gavin; Warren, Narelle; Ponsford, Jennie
ABSTRACT: Primary objective: Increasing physical activity (PA) among people with severe traumatic brain injury (TBI) represents an important long-term rehabilitation goal. To design effective interventions to promote PA, the factors associated with PA engagement post-TBI need to be understood. Research design: A qualitative study design was employed to investigate the factors influencing PA engagement in people with severe TBI living in the community. Methods and Procedures: Face-to-face interviews were conducted with eight people with severe TBI three to five years post-injury. A constant comparative method of data collection and analysis was adopted. Main outcomes and results: Interviews were analysed using thematic analysis. Three themes were identified: continuance of self and PA (perception of self, stage of life, and PA normality), beliefs about PA (knowledge of PA and associated benefits), and purpose of PA engagement (reasons for being physically active). Lifelong PA habits and current life priorities impacted on PA engagement post-TBI and influenced whether TBI-associated impairments were considered as a barrier to PA. Conclusion: Among this group of people, PA engagement post-TBI was influenced by perceptions of lifelong PA habits and current life priorities. Interventions to increase PA need to address these perceptions and adapt PA to account for life priorities within the context of TBI-associated impairments.